Implementation of Inclusive Education at State Elementary School 003 Tebing, Karimun Regency - Susanti, Lala; Khairiyah, Karunia Yulinda; Dianasari, Eka Lenggang; Putri, Zulfiana Dessyka; Rahmad, Hari Adi (Journal of Nonformal Education and Community Empowerment, 2026)
Implementation of Inclusive Education in SDN 003 Tebing, Karimun Regency. Thesis. Extraordinary Study Program. Karimun University, 2025. This research on inclusive education creates a system that is equitable and just by providing equal opportunities for all students, including children with special needs, to be able to learn together in an environment that is supportive, friendly, and respects differences. This study uses a qualitative descriptive research type that aims to determine the implementation of inclusive education at SDN 003 Tebing, Karimun Regency. This study uses a case study methodology. Data collected from the initial source of the study is known as primary data. Interviews with class teachers and principals are the main data sources for this study. data collection methods used by researchers, observation, interviews and documentation. Good measuring instruments in research are usually called research instruments. Data analysis in qualitative research is carried out before entering the field, while in the field, and after completion in the field. The results of the research on the components of inclusive education implementation are: 1). SD Negeri 003 Tebing limits the acceptance of PDBK to a maximum of 20 students per year to maintain the quality of inclusive services. The school conducts tiered identification and has carried out assessments and collaborated with SLB and psychologists to improve the quality of inclusive education; 2). SD Negeri 003 Tebing has implemented the Independent Curriculum for regular students, but the modifications have not been based on a comprehensive assessment of the abilities and individual needs of inclusive students; 3). SD Negeri 003 Tebing does not yet have teachers with a PLB background, so learning for inclusive students is less than optimal. To overcome this, the school collaborates through weekly mentoring and routine therapy programs; 4). The role of GPK is very important in supporting effective and targeted inclusive learning. SD Negeri 003 Tebing also partners with SLB Negeri Karimun through weekly mentoring and routine therapy programs; 5). Inclusive schools still face obstacles in assessing class promotions because there are no specific guidelines and achievement indicators for PDBK, although appreciation for academic and non-academic achievements has been given; 6). Physical facilities and aids for children with special needs at SD Negeri 003 Tebing are still inadequate, so special policy and budget support from the government is needed to support inclusive education. The goal of inclusive education which guarantees access, participation, and learning success for all children will not be achieved optimally. It can be concluded that inclusive education at SD Negeri 003 Tebing has realized fair, equal, and friendly education for all students without discrimination.